Konsep Manajemen Pelatihan Dakwah - Kusnawan, Aep (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2008)
The most of daâwah training programe can be designed and practed in various place. The conditions become logic if training tends to develop continuously and be studied as interesting field. Thus also concepts, theories, approach and terms of training, it will develop continuously. The condition be equal with its developing involve thingking, approach, methodology, regulating, actuating and evaluating. It is naturally that training constitute serious, interest and mempesona effort. Because it dual with growing human resources quality that more compatible.